ANALISIS KEBIJAKAN PENYEHATAN PERUSAHAAN DAERAH PERGUDANGAN DAN ANEKA USAHA (PD PAU) KOTA SAMARINDA - Dewi Sartika (Widyariset, 2014)
The regional enterprise which is the local government company is wholly or mainly derived from separated capital region. There are currently two mainstream paradigms (whose capital) in the management of regional enterprises. On one side, the region is one of the main instruments of Corporate Government in order to optimize local resources into investments that can increase revenue (profit) for regional own revenue. On the other side, the role of government as a public servant (public service) requires the regional enterprise not only for profit per se, but more expected to be a medium in order to carry out government functions and public services to accelerate the development process. Regional Enterprise Warehousing and Business Miscellaneous (PD PAU) Samarinda was originally formed to perform a warehousing arrangement spread into the region in the middle of town, but in the course of subsequent, PD PAU had disoriented businesses and financial crisis, making PD PAU verge of bankruptcy with some complexity issues. In order to save the business of PD PAU, several steps can be taken by the City Government of Samarinda to restructure the PD PAU, requiring policy measures for restructuring efforts, such as reformulation of business vision, management restructuring, verification of balance sheet, business rela- tions expansion, and addition of new capital.